Critical overview of applications of genetic testing in sport talent identification - Roth, S. M. (Recent Patents on DNA & Gene Sequences, 2012)
Talent identification for future sport performance is of paramount interest for many groups given the challenges of finding and costs of training potential elite athletes. Because genetic factors have been implicated in many performance- related traits (strength, endurance, etc.), a natural inclination is to consider the addition of genetic testing to talent identification programs. While the importance of genetic factors to sport performance is generally not disputed, whether genetic testing can positively inform talent identification is less certain. The present paper addresses the science behind the genetic tests that are now commercially available (some under patent protection) and aimed at predicting future sport performance potential. Also discussed are the challenging ethical issues that emerge from the availability of these tests. The potential negative consequences associated with genetic testing of young athletes will very likely outweigh any positive benefit for sport performance prediction at least for the next several years. The paper ends by exploring the future possibilities for genetic testing as the science of genomics in sport matures over the coming decade(s).